Pengaruh Green Finance Terhadap Nilai Perusahaan Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia - Yulianti, Nur Afni; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to find out and analyze how the influence of green finance affects the value of infrastructure Industrial companies listed on the Indonesia Stock Exchange. This study uses quantitative methods. The site of this study was conducted on infrastructure companies listed on the Indonesia Stock Exchange for the period 2020-2022 www.idk.go.id. The study will be conducted in November 2023 until its completion. The subjects of this study are infrastructure companies listed on the Indonesia Stock Exchange in the period from 2020 to 2022. The sample was selected based on the random sampling method, with some criteria 54 samples could be obtained. Research results show Green finance has a significant positive effect on Company Value in Infrastructure companies listed on the IDX 2020-2022 with an r-square value of 0.24, meaning that green finance is able to influence company value by 24% Keywords: Green Finance And Company Value